The Philosophy of Illumination: Esotericism in Shihāb ad-Dīn Suhrawardī’s Sufism - Assya'bani, Ridhatullah; Falach, Ghulam (UIN Sunan Kalijaga Yogyakarta, 2022)
Discussing Suhrawardī, certainly, cannot be separated from his concept of thinking about illumination (ḥikmat ishrāqiyyat), which has contributed to the foundation of human knowledge and awareness. The research question in this paper is how esotericism in Shihāb ad-Dīn Suhrawardī’s Sufism relates to the philosophy of Illumination. The discussion of this study is based on qualitative library research. In each section, this paper is supplemented with an explanation using the methods of description, interpretation, and data analysis to build a consistent and thorough understanding. This paper found that, according to Suhrawardī, knowledge is the presence of an object to know. Knowledge can only be attained by the mystic into the inner sanctum of higher visionary experiences (mushāhadat wa mukāshafat), not merely through logical reasoning. To achieve the truth of implicit knowledge, the philosophy of illumination suggested the combination of reason and intuition, which are complementary to one another. Regarding esotericism, in this case, the soul is interpreted as a part of the realm of light, but it is trapped in darkness, so spiritual training must be carried out in the spirit of soul-giving. Suhrawardī believes that only a clean soul can be connected to the divine light, wherein at that level, one can get intuitive wisdom, or in Sufism, it is called the laduni knowledge.